Establishment of electrochemical methods to examine the adsorption of flotation surfactants onto a mineral surface. Issue 5 (18th February 2020) - Guo, Bao; Lin, Xiaohui; Fu, Weng; Ku, Jiangang
Abstract: BACKGROUND: Significant efforts have been devoted to examine the adsorption of flotation surfactants in both mechanistic studies and process implementations. However, quantitative electrochemical methods for flotation surfactant adsorption examination have not been well‐established, despite of their low‐cost, accurate, in‐situ nature. RESULTS: In this paper, voltametric measurement was proven to quantitatively examine the adsorption of activating copper and lead ions onto a pyrite surface. The activation was achieved by abrading minerals in a heavy‐metal‐bearing solution and the measurements were performed by transferring the minerals to a solution free of those heavy metals. This provided a simple but realistic simulation of the mineral grinding process and simplified the adsorption quantification by excluding any other irrelevant electrochemical reactions near the surface. Reliable electrochemical impedance spectroscopy (EIS) upon adsorption with convincing physical models for interpreting the interfacial structures also were obtained in this paper. The additional pseudocapacitive behaviour of the copper sulfide surface layer led to an increased capacitance of the measured EIS. A resistive but ion‐permeable xanthate adsorption layer exhibited its own relaxation process. Voltammetry and impedance studies showed that cyanide competed with both copper and lead for their adsorption, whereas lead activation showed greater tolerance to cyanide than copper did. CONCLUSION: Electrochemical methods have been established to examine the adsorption of copper, lead and xanthate onto pyrite surface, in relation to various flotation conditions, which exhibited significant implication to the flotation of pyritic gold ore using cyanide‐bearing water. © 2020 Society of Chemical Industry